Migration and empire - Harper, Marjory (Oxford history of the British Empire. Companion series., 2010)
A unique comparative overview of the motives, means and experiences of three main flows of empire migrants from the 19th century to the post-colonial period, this book looks at the complex relationship between migration and empire.